I belong; hence, I engage? A cohort study of transitions between school engagement classes and academic achievement: The role of relational school climate - Katsantonis, Ioannis (My University, 2024)
The role of the school climate in buffering disengagement remains relatively underresearched. The present study examined transitions between classes of early adolescents’ school engagement and relational school climate factors influencing classes of students’ (dis-)engagement, and how these were linked with academic achievement in mid-adolescence. A representative sample of 3,643 early adolescents (48.72% females) from the Growing Up in Australia cohort study was utilised. Latent transition analyses indicated three classes of school engagement, namely mostly disengaged, moderately engaged and highly engaged. Significant transitions were found between classes with fewer students becoming moderately engaged and mostly disengaged. Having a positive teacher–student relationship and higher feelings of school belonging predicted membership to the highly engaged classes. Highly engaged students were fewer by age 12 but had the best achievement only in numeracy, writing and spelling tests at age 14/15. The study underscores the importance of positive relational school climate for fostering school engagement and achievement.
The Australian Educational Researcher
Keywords: Adolescents and youth; Learning, education and training